A study on promotional effort provided by PASDEC Corporation / Maswati Rohani - Rohani, Maswati (2006)
The study proposes about the promotional effort provided by PASDEC Corporation. It uses a sample of 120 respondents among the PASDEC Corporation’s customers. The aim of the study is to measure the promotional effort done by PASDEC Corporation. The population of the research is the PASDEC Corporation’s customers which selected from 4 areas that are from the Carnival, showroom, exhibition and selling promotion and marketing department counter. The questionnaire will distribute the researcher. The questionnaire contains 6 section that to be answered by the selected respondent. 120 respondents were selected from the 200 population. This selection of the respondent was based on the non-probability sampling technique and the cluster sampling has been used to select the respondent.